Ultraviolet radiation stress response of haploid and diploid spores of Mazzaella laminarioides: Do bio-optical traits matter? - Navarro Martinez, Nelso Patricio; Huovinen, Pirjo; Jofre, Jocelyn; Gomez, Ivan (My University, 2021)
Early stages of macroalgae are known to be more vulnerable to changes in the abiotic environment than their adult phases. However, in algal groups attaining intricate life-cycles, the ecophysiological responses of haploid and diploid propagules have not been sufficiently studied. In the present study, stress responses of haploid tetraspores and diploid carpospores of sub-Antarctic red alga Mazzaella laminarioides exposed to ultraviolet (UV) radiation were studied. We tested the hypothesis that UV stress responses of two types of spores attaining similar size are determined by light use characteristics by comparing the photobiological and bio-optical traits. Fluorescence-based photosynthetic efficiency was measured during a 5-h exposure and after a 5-h recovery. Germination and growth of spores exposed to UV treatments were also assessed. Diploid carpospores exhibited higher chlorophyll a content and higher absorption in the UV band than tetraspores. Although the maximal quantum yield was higher in carpospores than tetraspores, no differences in light demands were detected. Exposure to photosynthetically active radiation (PAR) caused inhibition of photosynthetic activity only in carpospores (43%), while exposure to a combination of PAR + UV reduced the maximal quantum yield significantly in tetraspores (36%) and carpospores (60%). In both types of spores, a recovery from UV stress was observed, allowing their germination and further development. The different responses to radiation found in haploid and diploid propagules highlight the ecophysiological versatility of different life-cycle phases to cope with light stress factors ensuring finally successful recruitment and survival.
Keywords: isomorphic phases; propagules; reproductive cycles; stress tolerance; sub-antarctic region